2016
DOI: 10.1016/j.nanoen.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Revealing optically induced dipole-dipole interaction effects on charge dissociation at donor:acceptor interfaces in organic solar cells under device-operating condition

Abstract: Organic materials normally have low dielectric constants and are often formed with high electron-hole binding energy, which are detrimental to the generation of photovoltaic actions in solution-processing thin-film solar cells. Here, we show that optically induced dipoledipole interaction can largely decrease the electron-hole binding energy at donor:acceptor (D:A) based on the PTB7:PCBM bulk-heterojunctions. Our experimental measurements combine (i) double-beam 325 nm and 532 nm excitations to establish dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…However, V oc difference is negligible for these two devices therefore, it is expected that the interface is somehow similar. Moreover, it has been recently shown by us that at V oc condition, when the built‐in field is balanced by an applied field, the optically generated dipoles become randomly oriented in the amorphous PTB7 transport layer, diminishing the dipole effects on photovoltaic actions . Therefore, at V oc condition under illumination, photogenerated dipoles in PTB7 layer are random and similar V oc is expected for both devices.…”
Section: Resultsmentioning
confidence: 78%
“…However, V oc difference is negligible for these two devices therefore, it is expected that the interface is somehow similar. Moreover, it has been recently shown by us that at V oc condition, when the built‐in field is balanced by an applied field, the optically generated dipoles become randomly oriented in the amorphous PTB7 transport layer, diminishing the dipole effects on photovoltaic actions . Therefore, at V oc condition under illumination, photogenerated dipoles in PTB7 layer are random and similar V oc is expected for both devices.…”
Section: Resultsmentioning
confidence: 78%
“…Our early studies have shown that magneto-J sc can be used as a method in situ to dynamically monitor the dissociation at D:A interfaces in organic solar cells under device operation. [41][42][43][44][45] Normally, magneto-J sc can be established by gradually increasing the magnetic field while monitoring photocurrent J sc . Essentially, using magneto-J sc to monitor the charge separation at D:A interfaces is based on following three subsequent processes.…”
Section: Context and Scalementioning
confidence: 99%
“…We know that polaron pairs can be largely formed towards light-emitting excitons in OLEDs under electrical injection 32, 33 . It has been experimentally observed that an external magnetic field can conveniently change the populations on the singlet and triplet polaron pairs, leading to magneto-EL 18, 34, 35 and magneto-current 36, 37 due to largely different recombination rates associated with singlets and triplets. Therefore, magneto-EL can be measured at two different conditions: constant-current and constant-voltage modes, while monitoring the EL intensity with scanning magnetic field 18, 19, 38 .…”
Section: Resultsmentioning
confidence: 99%